Genetic evaluation of White Leghorn layers under reciprocal recurrent selection - Ramesh Kumar; S Kalra; Satbir Singh; B Parkash (Journal of Livestock Biodiversity, 2025)
Present study revealed that crossbreds were marginally superior in most of the performance traits than the purebreds. AFE of purebreds was lower than observed for crossbreds in all generations except G4 , G5 and G6  generations. The EN was more during the initial three generations of study whereas it declined sharply in the fourth and sixth generations.  No definite trend was observed for the difference in EW of two reciprocal crosses in all the generations under study.  EN was found to be more important than EW in determining the EM. Differences in the mean over the generations may be accounted for by the effect of selection and environmental factors. .Heritability estimates for BW20 , BW40, and AFE were moderate to high, but EN was low heritable.  Heritabilities of EM, EM/BW20 and EM/AFE were moderate indicating that some form of family selection may be effective for their improvement.  Standard errors of heritability estimates were small suggesting that a reasonably high degree of reliance can be placed on these estimates. Large standard errors of heritabilities of traits of crossbreds than the purebreds might be due to smaller population size in comparison to purebred strains. . Body weight, age at first egg and egg number were negatively correlated with each other both at genetic and phenotypic levels. Egg weight was positively correlated with body weights at phenotypic level both in purebreds and crossbreds but negatively genetically correlated in purebreds and reverse was observed in crossbreds. Most of the phenotypic correlations were highly significant both in purebreds and crossbreds.  It might be concluded that heavier birds lay large sized eggs but higher weight during laying period is not a desirable proposition. . Results suggest the use of RRS selection schemes for further improvement of egg production and its component traits of hybrid layer.